The Stranger Danger: Exploring Surveillance, Autonomy, and Privacy in Children’s Use of Social Media - Nolan, J.; Raynes-Goldie, Kate; McBride, M. (Canadian Association for Young Children, 2011)
The threat of online ‘stranger danger’ is a dominant theme in mainstream Western media reporting about children and the Internet. This climate of fear and moral panic has certain parents seeking increasingly restrictive measures to keep their children ‘out of harm’s way’ (Barnes, 2006; Boyd & Jenkins, 2006; Chung & Grimes, 2005; Livingstone, 2009; Marwick, 2008). While the stranger danger meme has proven profitable for companies selling parental surveillance software (i.e. ‘censorware’), research indicates that children are safer now than a decade ago (Boyd & Jenkins, 2006; Lumber, 2009; Statistics Canada, 2003; Wastler, 2010; Wolak, Finkelhor & Mitchell, 2004; Wolak, Finkelhor, Mitchell & Ybarra, 2008; U.S. Department of Health and Human Services, 2010). However, it is the concern about risk, rather than an increase in actual risk, which is the story behind the headlines (Kelley, Mayall & Hood, 1997).